NILAI-NILAI SUFISTIK DALAM NOVEL HAFALAN SHALAT DELISA KARYA TERE LIYE - Muhammad Isnaini; Al Fadhli Tasman (Bahasa Indonesia, 2025)
This research discusses the Sufistic values ​​contained in the novel Hafalan Shalat Delisa. Through critical and interpretive reading, this research aims to explore the Sufistic values ​​shown and applied in the novel. Even though this work is not the work of a Sufi, it contains Sufistic values ​​in it. Apart from that, this research will also discuss Sufism and its teachings and values, which can provide insight and guidance for readers on how to live a more balanced and calming life in modern life. This research is library research, using the content analysis method (content analyst). Based on the results of the research that has been carried out, it was found that in the novel Hafalan Shalat Delisa there are the following things. Sufistic values ​​which include; The values ​​of sh{abr, tawakkal, ridha', mahabbah, syukr, and taubah. These values ​​have urgency in the life of modern society. The Sufistic values ​​contained in the novel Hafalan Shalat Delisa can be a turning point for someone in restoring their spiritual condition, especially in the modern era.